2005
DOI: 10.1099/mic.0.27485-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression in trap cells and vegetative hyphae of the nematophagous fungus Monacrosporium haptotylum

Abstract: Nematode-trapping fungi enter the parasitic stage by developing specific morphological structures called traps. The global patterns of gene expression in traps and mycelium of the fungus Monacrosporium haptotylum were compared. The trap of this fungus is a unicellular spherical structure called the knob, which develops on the apex of a hyphal branch. RNA was isolated from knobs and mycelium and hybridized to a cDNA array containing probes of 2822 EST clones of M. haptotylum. Despite the fact that the knobs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
(47 reference statements)
0
58
0
Order By: Relevance
“…The global patterns of gene expression has been studied in traps and mycelium of M. haptotylum (Ahre´n et al, 2005). The advantage of using M. haptotylum is that during growth in liquid cultures with heavy aeration, the connection between the traps (knobs) and mycelium can be broken easily and the knobs can be separated from the mycelium by filtration.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The global patterns of gene expression has been studied in traps and mycelium of M. haptotylum (Ahre´n et al, 2005). The advantage of using M. haptotylum is that during growth in liquid cultures with heavy aeration, the connection between the traps (knobs) and mycelium can be broken easily and the knobs can be separated from the mycelium by filtration.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The trapping cells of nematodetrapping fungi and the appressoria formed by plant-pathogenic fungi have several structural and functional similarities (9). Both are specialized infection structures that develop from hyphae.…”
Section: Cell Surface Proteins (I) Proteins Containing the Wsc Domaimentioning
confidence: 99%
“…The isolated knobs retain their function as infection structures, i.e., they can trap and kill nematodes (8). A microarray analysis based on a limited set of expressed sequence tag (EST) probes compared the gene expression in knobs with that in vegetative mycelia (9). The result showed that 23% of the genes were differentially expressed; many were homologous to genes involved in the regulation of morphogenesis and cell polarity, stress response, protein synthesis and protein degradation, transcription, and carbon metabolism.…”
mentioning
confidence: 99%
“…While 12 nuclei were observed in A. amerospora stained by DAPI, and 6–20 nuclei were observed in A. conoides 8 . In the past 50 years, researchers have made great efforts in identifying pathogenicity-related genes 46, 9 , and in understanding the difference between vegetative mycelia and traps 1013 . Recently, three species of NTF producing different traps were individually sequenced 11, 12, 14 , in which the trap cell proteome of the fungus M. haptotylum 15 , and the proteomic and transcriptional analyses of cell wall related proteins of Arthrobotrys oligospora 16 , were characterized.…”
Section: Introductionmentioning
confidence: 99%